Establishment of a family production unit of Pleurotus spp. in a rural community of Oaxaca, Mexico. - Vargas-Mendoza, Yanet; Santiago-García, Patricia Araceli; Soto-Castro, Delia; Gaitán Hernández, Rigoberto (Agricultura, Sociedad y Desarrollo, 2024)
Family Production Units (FPUs) are a strategy in low-cost food production for the rural population, as a system of associativity that allows the involvement of its members. The study’s objective was to establish a mushroom (Pleurotus spp.) FPU in the community of San Juan Yatzona, Oaxaca, as an alternative to contribute to food security. The participative action research methodology was followed for the integration, organization, and construction of the FPU. Pleurotus pulmonarius and P. ostreatus were grown in wheat straw (S) and straw with corn stubble (SS 1:1) under rustic conditions. The productivity was evaluated, the cost analysis of the project, and social evaluation through the logical framework methodology were carried out. The FPU was established on a surface of 56 m2, subdivided into zones to carry out the total process. The highest productivity of P. pulmonarius was found in wheat straw, while for P. ostreatus, it was in straw with corn stubble 1:1, with a biological efficiency of 72.52% and 47.46%, respectively. In general, the most productive species was P. pulmonarius, statistically different from P. ostreatus, while there were no significant differences between the substrates. The total investment cost for this FPU was $11,156 MX, regarded as affordable for the members involved. The training and development of abilities in women from the community for mushroom production allowed the establishment of the FPU as an alternative to contribute to food security.